Nothing Absolute : German Idealism and the Question of Political Theology - Chepurin, Kirill (Book collections on Project MUSE., 2021)
Against traditional approaches that view German Idealism as a secularizing movement, this volume revisits it as the first fundamentally philosophical articulation of the political-theological problematic in the aftermath of the Enlightenment and the advent of secularity.